Seed Biology - Jimenez-Lopez, Jose C. (IntechOpen, 2017)
The seed can be considered the most important plant reproductive element, as a dispersal unit for a successful reproduction in all gymnosperms and flowering plants. The formation of the seed is part of the process of reproduction in seed plants, starting with a mature ovule and following with the fertilization by pollen and some growth within the mother plant to the final outcome of an embryo developed from the zygote, the seed coat from the integuments of the ovule, and a nurturing endosperm in several species. Thanks to this key element as it is the seed, the spermatophytes now dominate all types of biological niches on land, from forests to grasslands, both in hot and cold climates. In this metadata information era, we have the chance for a deeper understanding of seed physiological and developmental processes in order to provide the fundamental basis for making plant (seed) biology research relevant and productive,coping with future challenges.